Synthesis of dendritic silver nano powder using pulsing electrolysis in ammonia solution - Soltanzadeh A.; Shahini S.; Rashchi F.; Saba M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A method to produce nano silver structures with high purity is pulsing electrolysis. In this paper the effects of potential, ammonia concentration (NH3), silver ion concentration [Ag+], total time, Ton, Toff and Trev on this process were studied. The considered parameters were varied as follows: electrical potential = 5 – 10 V; [NH3] = 40 – 80 g/L; [Ag+] = 0.1 – 0.5 g/L; total time = 15 – 30 min; Ton = 1 – 8 ms; Toff = 1 – 8 ms; and Trev = 0 – 4 ms. In order to optimize these parameters, the fractional factorial design of experiments was used. A silver dendritic structure was produced with nano size arm. The phase composition and morphology of the synthetized dendritic silver nanostructures was determined by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The optimum condition to synthesize the dendritic silver nano powders were 7.52 V; [NH3] = 64.75 g/L; [Ag+] = 0.45 g/L; total time = 17.59 min; Ton = 6.97 ms; Toff = 4 ms; and Trev = 1.89 ms. A mathematical model was also presented. The predicted silver nano size dendrite arm at the optimum condition was found to be 87.29 nm which was very close to the experimental value of 90 nm.